Pengaruh Suhu pada Ekspresi Pretrombin-2 Manusia Rekombinan di Escherichia coli ER2566 - Silaban, Saronom; Simorangkir, Murniaty; Maksum, Iman Permana; Subroto, Toto; Hasan, Khomaini (Jurnal Sains Indonesia, 2018)
Human recombinant prethrombin-2 (rhPT-2) was expressed in Escherichia coli. Previous studies reported that the expression of rhPT-2 in E. coli tends to formed inclusion body. This study aims to determine the effect of temperature on the expression of rhPT-2 in E. coli ER2566. This study begins with the isolation of recombinant plasmids, competent cell preparation and transformation of competent cells of E. coli ER2566 strain, and rhPT-2 gene expression with various induction temperatures 12, 18, 22 and 30Â°C. Characterization results showed that the induction temperature of 22Â°C was the optimum temperature of rhPT-2 gene expression as a soluble fraction in E. coli ER2566 with IPTG concentration 0.1 mM. These results prove that the temperature affects the expression of rhPT-2 in E. coli ER2566.